Determining Economic Losses and Factors Influencing Flood, Drought And Earthquake Risk Perception in Disasters-Prone Areas of Punjab, Pakistan - Ahmad , Dilshad; Shah, Salyha Zulfiqar Ali; Ayub, Muahammad (Pakistan Journal of Humanities and Social Sciences, 2022)
Climate-based natural disaster intensity and destruction severity have risen multifold particularly in developing countries owing to an inadequate understanding of disaster risk perception. In using the household data of 398 respondents and the ordered probit model this study focused to investigate the factors influencing flood, drought, and earthquake risk perception in Punjab, Pakistan. In selected study areas, the majority of respondent’s likelihood perceived of happening disasters which caused financial losses and severely influenced their livelihood. Disasters-prone-area inhabitants’ inadequate understanding of mitigation measures has increased their vulnerability as they have become ineffective to overcome such natural disasters' severe impacts. Empirical estimates of the study indicated as sources of income generating, education level, gender, status, and age of household significantly affect the respondent's risk perception about flood, drought, and earthquake. Females in contrast to male respondents have a limited understanding of mitigation measures and are not as much of capable of controlling disasters as they have become more vulnerable related to disaster effects. In developing the disaster-prone communities' socioeconomic status urgent-based measures are required such as the understanding of the disaster gender-based gap needs to be reduced through better household appreciative vigilance and alleviation of floods, drought, and earthquake disasters.